Efficacy of free gingival graft in the treatment of Miller Class I and Class II localized gingival recessions: A systematic review - Sukhada Dileep Deo; Sharath Kumara Shetty; Anita Kulloli; Ruchira Chavan; Poonam Dholakia; Shruti Ligade; Gopalakrishnan Dharmarajan (Wolters Kluwer Medknow Publications, 2019)
Background: Currently, the leading theme in mucogingival surgery is the correction of gingival recession defects. Free gingival graft (FGG) has been successfully in use in this category of reconstructive therapeutic modality. Objectives: The aim of this systematic review was to evaluate the literature with respect to efficacy of FGG in the management of Miller Class I and II localized gingival recessions. Data Sources: Search strategies were performed via electronic database which included Pubmed-Medline, Google scholar and manual search using University library resources. Two reviewers assessed the eligibility of the studies. Study Eligibility Criteria: Controlled clinical trials, randomized clinical trials and longitudinal studies evaluating recession areas treated by FGG with minimum of 6 months follow up were included. In-vitro and animal studies, studies mainly done on Miller Class III and IV gingival recession defect, studies on multiple gingival recessions and case series and case reports were excluded from the search. Results: The electronic and manual search identified a total of 557 articles. A final screen consisted of 39 articles out of which 17 articles were selected for full-text assessment. Finally, 7 articles were selected for detailed evaluation for this systematic review. FGG has shown significant results in all the studies except for one study. Conclusion: FGG produces substantial results, however, highly depends on the case selection and operator's skill and experience. FGG gives an impression of being the best alternative option in zones where gingival recession presents with inadequate width of attached gingiva and depth of vestibular fornix.